Efforts to Improve Perinatal Outcomes for Women Enrolled in Medicaid. Issue 2 (August 2015) - Daniel-Robinson, Lekisha; Cha, Stephen; Lillie-Blanton, Marsha
<x xml:space="preserve">Abstract</x> Improving women's health and perinatal health outcomes is a high priority for Medicaid, the jointly financed federal–state health coverage program. The authorities provided by the Affordable Care Act give Medicaid new resources and opportunities to improve coverage and perinatal care. Given that the Medicaid program currently covers almost half of all births in the United States, the Centers for Medicare and Medicaid Services, working in partnership with states and other stakeholders, is using new and existing authorities to improve birth outcomes. Quality measurement, quality-improvement projects, and expanded models of care underscore the major quality approach of the center. As an outgrowth of an expert panel that included membership of several state Medicaid medical directors, Medicaid providers, and consumer representatives, the Centers for Medicare and Medicaid Services' Center for Medicaid and CHIP Services launched the Maternal and Infant Health Initiative, which aims to increase postpartum visit rates and the use of effective contraception among women covered by Medicaid. This Initiative provides focus on key opportunities and strategies to improve the rate, measurement, timing, and content of postpartum visits. Additionally, a focus on contraception will serve to improve pregnancy planning and spacing and prevent unintended pregnancy. As the Initiative evolves, the Center for Medicaid and CHIP Services plans to identify policy, service delivery, and reimbursement policies to advance the Initiative's goals and improve outcomes for women covered by Medicaid.